(untitled) (Academia Journal of Medicine, 2023)
Lesion sterilization tissue repair (LSTR) is an emerging approach in dentistry, aimed at eliminating infectious microorganisms from the root canals and promoting tissue repair. This review provides a comprehensive overview of the principles, techniques, and recent advances in LSTR. The traditional root canal treatment focuses on complete debridement and disinfection of the root canal system. However, LSTR offers an alternative approach by employing a triple antibiotic paste (TAP) consisting of metronidazole, ciprofloxacin, and minocycline. This antibiotic combination has shown promising results in eliminating the root canal microbiota, particularly in cases of immature teeth with open apices and necrotic pulps.